Cutting activates a 46-kilodalton protein kinase in plants. - Usami, S (1995)
Using SDS/polyacrylamide gels that contained myelin basic protein, we identified a 46-kDa protein kinase in tobacco that is transiently activated by cutting. Although the activity of the kinase was rarely detectable in mature leaves, marked activity became apparent within several minutes after isolation of leaf discs and subsided within 30 min. In the presence of cycloheximide (CHX), the kinase activity did not diminish after the isolation over the course of 2 hr, suggesting that protein synthesis was not required for the activation of the kinase. A second cutting of leaf discs between 30 min and 60 min after the isolation failed to activate the kinase, whereas a second cutting given 3 hr after isolation apparently activated the kinase. These results suggest that the 46-kDa protein kinase is desensitized immediately after the first activation, which can be blocked by CHX, but the response ability recovers with time. When protein extracts containing the active kinase were treated with serine/threonine-specific or tyrosine-specific protein phosphatase, the kinase activity was abolished. After immunoprecipitation with antibody against phosphotyrosine, activity of the kinase was recovered in the immunoprecipitate. These results suggest that the active form of the kinase is phosphorylated at both serine/threonine and tyrosine residues. It seems likely that the 46-kDa protein kinase can be activated by dual phosphorylation. The activity of a 46-kDa protein kinase was also detected in leaves of a wide variety of plant species including dicotyledonous and monocotyledonous plants. We propose the name PMSAP (plant multisignal-activated protein) kinase for this kinase because the kinase was also activated by various signals other than cutting.